2005
DOI: 10.1002/pon.953
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in prostate cancer survivors and their partners

Abstract: We examined posttraumatic growth (PTG) in men treated for prostate cancer and their partners 1 year after surgery. Levels of PTG in prostate cancer survivors and their partners were similar and modest. For survivors, higher levels of presurgery negative affect, and coping by using positive reframing and emotional support were associated with higher levels of PTG 1 year following surgery. For partners, PTG 1 year after the patient's surgery was higher in partners who were partnered to employed patients, were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
158
6
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(197 citation statements)
references
References 48 publications
(110 reference statements)
22
158
6
9
Order By: Relevance
“…For example, many cancer survivors report being closer to their spouses, families, and friends than they were prior to their cancer (Thornton & Perez, 2006). Cancer survivors also report a renewed appreciation for life, meaning, and purpose (Thornton & Perez, 2006).…”
Section: Stress-related Growth After Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…For example, many cancer survivors report being closer to their spouses, families, and friends than they were prior to their cancer (Thornton & Perez, 2006). Cancer survivors also report a renewed appreciation for life, meaning, and purpose (Thornton & Perez, 2006).…”
Section: Stress-related Growth After Cancermentioning
confidence: 99%
“…This growth and positive change can occur in many life domains, including interpersonal relationships, life philosophies, goals, values, spirituality, and lifestyle (Aldwin et al, 2009;Tomich & Helgeson, 2002). For example, many cancer survivors report being closer to their spouses, families, and friends than they were prior to their cancer (Thornton & Perez, 2006). Cancer survivors also report a renewed appreciation for life, meaning, and purpose (Thornton & Perez, 2006).…”
Section: Stress-related Growth After Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The better outcomes in role emotional functioning and mental health among patients compared with NORM may reflect a response shift related to post-traumatic growth. 24 The sexual function reported by the patients in our study is probably confounded by radiotoxicity as the post-RT prevalence of ED increases with time. 25 The magnitude of RT as a confounding factor is impossible to estimate because we did not have a control group that received RT monotherapy in our study and the post-RT rates of ED reported in the literature vary from 8 to 85%.…”
Section: Discussionmentioning
confidence: 65%
“…Es justamente a este nuevo Yo caracterizado en términos heroicos, una persona empática que sabe reconocer los valores importantes de la vida, que establece relaciones intimas y funcionales con la gente de su entorno, que sabe disfrutar de las pequeñas cosas de la vida, que conecta profundamente con las aspectos trascendentales de la existencia... el Yo socialmente celebrado en las ceremonias publicas de la cultura hegemónica del cáncer y los medios de comunicación. Es conveniente recordar que ya en los primeros modelos de CPT elaborados por Tedeschi y Calhoun (99) se especifica el papel preeminente de determinados rasgos del sujeto y esfuerzos de afrontamiento como elementos centrales para la emergencia de crecimiento personal, es decir, el CPT no es consecuencia de haber padecido un cáncer, del hecho en si, sino de una determinada manera de relacionarse con y afrontar lo traumático En términos culturales, como indican Thornton y Pérez (100) , resulta relevante que la mayoría de estudios realizados en CPT oncológico sea en muestra de mujeres con cáncer de mama, lo que informa de una conexión que, a la par de sesgar los resultados, expresa la cercanía entre este tipo de tumor y el crecimiento personal. En el número de noviembre 2001 de Harper's Magazine Barbara Ehrenreich (101) publicó un extenso artículo titulado Welcome to Cancerland que en escaso tiempo se convirtió en cita de referencia para gran parte de las culturas subalternas oncológi-cas.…”
Section: Las Narrativas Heroicas Facilitan Tam-unclassified